Data damage assessment and recovery algorithm from malicious attacks in healthcare data sharing systems - Haraty, Ramzi A. (2016)
In a data sharing system in a cloud computing environment, such as health care system, peers or data sources execute transactions on-the-fly in response to user queries without any centralized control. In this case confidential data might be intercepted or read by hackers. We cannot consider any centralized control for securing data since we cannot assume any central third party security infrastructure (e.g., PKI) to protect confidential data in a data sharing system. Securing health information from malicious attacks has become a major concern. However, securing the data from attacks sometimes fail and attackers succeed in inserting malicious data. Hence, this presents a need for fast and efficient damage assessment and recovery algorithms. In this paper, we present an efficient data damage assessment and recovery algorithm to delete malicious transactions and recover affected transactions in a data source in a health care system based on the concept of the matrix. We compare our algorithm with other approaches and show the performance results.